1999
DOI: 10.2307/2648085
|View full text |Cite
|
Sign up to set email alerts
|

Rectangularization revisited: Variability of age at death within human populations*

Abstract: Rectangularization of human survival curves is associated with decreasing variability in the distribution of ages at death. This variability, as measured by the interquartile range of life table ages at death, has decreased from about 65 years to 15 years since 1751 in Sweden. Most of this decline occurred between the 1870s and the 1950s. Since then, variability in age at death has been nearly constant in Sweden, Japan, and the United States, defying predictions of a continuing rectangularization. The United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
378
0
50

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(447 citation statements)
references
References 18 publications
19
378
0
50
Order By: Relevance
“…Inspired by this fact, some gerontologists have concluded that future life expectancy at birth will unlikely exceed 85 years (Fries 1980;Carnes and Olshansky 2007). The problem with such a hypothesis is that-although the virtually zero background mortality leaves no scope for improvement-we cannot (yet) see any slowdown or convergence of life expectancy in the data (Wilmoth 1997(Wilmoth , 1999. This means that recent advances of life expectancy must have originated from a process that is reflected by a change of the Gompertz parameters.…”
Section: The Gompertz-makeham Law Of Mortalitymentioning
confidence: 99%
See 3 more Smart Citations
“…Inspired by this fact, some gerontologists have concluded that future life expectancy at birth will unlikely exceed 85 years (Fries 1980;Carnes and Olshansky 2007). The problem with such a hypothesis is that-although the virtually zero background mortality leaves no scope for improvement-we cannot (yet) see any slowdown or convergence of life expectancy in the data (Wilmoth 1997(Wilmoth , 1999. This means that recent advances of life expectancy must have originated from a process that is reflected by a change of the Gompertz parameters.…”
Section: The Gompertz-makeham Law Of Mortalitymentioning
confidence: 99%
“…1900-1924and 1975-1999. Dashed blue line: Survival function in 1975-1999. Solid orange line: Survival function in 1900-1925 First, a rectangularization or compression of morbidity is clearly visible.…”
Section: Survival Probabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The process of progressive rectangularization of the survival function has been documented also by Wilmoth and Horiuchi (1999) for a sample of countries that have undergone the demographic transition and, more recently, by Strulik and Vollmer (2013), for the period 1900-2000 in a large cross-section of countries. 14 The same pattern has been documented for the preindustrial period 1000-1900 by de la Croix and Licandro (2012) using a cross-country data set on the mortality of famous individuals.…”
mentioning
confidence: 99%